The Influence of Nano-Encapsulation of Melastoma malabathricum L. Fruit Extract to Lipid Profile of Broiler Chicken - Muhammad Dani; Rusman Rusman; Zuprizal Zuprizal (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
The aim of this research was to examine the impact of nano encapsulation of Melastoma malabathricum L. fruit extract as feed additive that was given through drinking water towards lipid profile of broiler chicken. Experimental design used in this research was completely randomized design using six increment treatments of Melastoma malabathricum L. fruit extract to the drinking water of the chicken each with five repetitions. Detail of treatment rations were as follow: T0 drinking water treatment without feed additive (negative control), T1 drinking water treatment + 0.2 mg/kg body weight simvastatin (positive control), T2 drinking water treatment + 1.5% Melastoma malabathricum L. fruit extract, T3 drinking water treatment + 3.0% Melastoma malabathricum L. fruit extract, T4 drinking water treatment + 1.5% nano encapsulation of Melastoma malabathricum L. fruit extract, T5 drinking water treatment + 3.0% nano encapsulation of Melastoma malabathricum L. fruit extract. Observed Parameters were the blood lipid profile, cholesterol of meat and crude fat of meat. The results showed that adding the nano encapsulation of Melastoma malabathricum L. fruit extract did not give significant effect (P>0.05) on blood lipid profile and crude fat of the thigh and breast of the broilers. Addition of nano encapsulation of Melastoma malabathricum L. fruit extract gives real impact (P<0.05) toward reduction of broiler’s meat cholesterol. The conclusion of this research is that giving nano encapsulation of Melastoma malabathricum L. fruit extract is able to improve lipid profile of broiler, which is in the amount of meat’s cholesterol.